Segmentation of the fascia lata and reproducible quantification of intermuscular adipose tissue (IMAT) of the thigh - Chaudry, Oliver; Friedberger, Andreas; Grimm, Alexandra; Uder, Michael; Nagel, Armin Michael; Kemmler, Wolfgang; Engelke, Klaus (Magnetic Resonance Materials in Physics Biology and Medicine, 2020)
Objective: To develop a precise semi-automated segmentation of the fascia lata (FL) of the thigh to quantify IMAT volume in T1w MR images and fat fraction (FF) in Dixon MR images. Materials and methods: A multi-step segmentation approach was developed to identify fibrous structures of the FL and combining them into a closed 3D surface. 23 healthy young men with low and 50 elderly sarcopenic men with moderate levels of IMAT were measured by T1w and 6pt Dixon MRI at 3T. 20 datasets were used to determine reanalysis precision errors. IMAT volume was compared using the new FL segmentation versus an easier to segment but less accurate, tightly fitting envelope of the thigh muscle ensemble. Results: The segmentation was successfully applied to all 73 datasets and took about 7 min per 28 slices. In particular, in elderly subjects, it includes a large amount of adipose tissue below the FL typically not accounted for in other segmentation approaches. Inter- and intra-operator RMS-CVs were 0.33% and 0.14%, respectively, for IMAT volume and 0.04% and 0.02%, respectively, for FFMT. Discussion: The FL segmentation is an important step to quantify IMAT with high precision and may be useful to investigate effects of aging and treatment on changes of IMAT and FF. ClinicalTrials.gov identifier NCT2857660, August 5, 2016. Trial registration: ClinicalTrials.gov identifier NCT2857660, August 5, 2016.
CRIS-Team Scopus Importer:2020-08-14
Keywords: Adipose tissue; Fascia lata; MRI